Gangguan Mental Emosional Siswa Sekolah Dasar - Prihatiningsih, Erika; Wijayanti, Yuni (HIGEIA (Journal of Public Health Research and Development), 2019)
Abstract. Mental disorders in children and adolescents are the focus of global health because of their relationship to suffering, functional impairment, stigmatized exposure, discrimination, and the potential for death. Based on global epidemiological data 12-13% of children and adolescents suffer from mental disorders. This study aims to determine the factors that affect emotional mental disorders in elementary school students. The cross-sectional method was used with 222 respondents from six different elementary schools. Chi-Square test analysis is used for data analysis. 121 (53.3%) subjects experienced symptoms of emotional mental disorders. The results show that the education level of the father (PR= 1,785 ;p <0.05), the level of family income per month (PR=2,345 ;p <0.05), sleep disorders (PR= 1,79 ;p <0.05), and vegetable consumption affects the incidence of emotional mental disorders (PR= 2,023; p <0.05) Keywords: children, elemtary school, mental health disorder Abstrak. Gangguan mental pada anak dan remaja menjadi fokus kesehatan global karena hubungannya dengan penderitaan, fungtional impairment, paparan stigma, diskriminasi, hingga potensi kematian. Berdsasarkan data epidemiologi global 12-13% anak dan remaja menderita gangguan mental. Penelitian ini bertujuan untuk mengetahui faktor yang memepengaruhi gangguan mental pada siswa sekolah dasar. Metode cross-sectional digunakan dengan jumlah responden 222 dari enam sekolah dasar yang berbeda. Analisis uji Chi-Square digunakan untuk analisa data. Hasil menunjukan 121 (53,3%) subjek terdeteksi mengalami gejala gangguan mental emosional, selanjutnya bahwa tingkat pendidikan ayah (PR=1,785; p<0,05), tingkat penghasilan keluarga per bulan (PR=2,345; p<0,05), gangguan tidur (PR= 1,79; p<0,05), dan konsumsi sayur mempengaruhi kejadian gangguan mental emosional (PR= 2,023; p<0,05). Kata kunci: anak-anak , gangguan mental emosional, sekolah dasar